FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pradesa, Endar (JURNAL FAIRNESS, 2019)
This study aims to influence profitability, sales growth, market valuation, company size, and audit quality to going concern audit opinion. The population in this study are all companies listed on the Indonesia Stock Exchange 2014-2017. The type of research in the research is quantitative research. The sampling technique used is a proposive sample and the selection of 69 units of company analysis. Models of analysis that are practical logistic regression. Audit quality was measured using the kaznik accrual discretionary model (1999). The result of the research shows that firm size has an effect on going concern audit opinion, while profitability, sales growth, market value, and audit quality have an effect on going concern audit opinion.